The Influence of Competitive Prices and Product Quality on Purchase Decisions of Cabbage Vegetables in Wuasa Village, North Lore District, Poso Regency - Arianto, Krisdian; Ponirin (PT. Global World Scientific, 2024)
This research aims to determine and analyze the influence of price and product quality simultaneously and partially on the decision to purchase cabbage in Wuasa Village, North Lore District, Poso Regency. The type of research used is descriptive verification research. The population of this study isThe exact number of cabbage buyers in Wuasa Village, North Lore District, Poso Regency. The sampling technique in this research used purposive sampling, with a sample size of 60 respondents. The data collection techniques used were observation, questionnaires and documentation. The scale used in this research is a Likert scale and the analytical tool used is multiple linear regression analysis. The results of this research show that price and product quality influence the decision to purchase cabbage in Wuasa Village, North Lore District, Poso Regency. Price influences the decision to purchase cabbage in Wuasa Village, North Lore District, Poso Regency. Product quality influences the decision to purchase cabbage in Wuasa Village, North Lore District, Poso Regency